Chronic Cough and Gastroesophageal Reflux in Children: CHEST Guideline and Expert Panel Report - Chang, Anne B. (Chest, 2019)
BACKGROUND: Whether gastroesophageal reflux (GER) or GER disease (GERD) causes chronic cough in children is controversial. Using the Population, Intervention, Comparison, Outcome (PICO) format, we undertook four systematic reviews. For children with chronic cough (> 4-weeks duration) and without underlying lung disease: (1) who do not have gastrointestinal GER symptoms, should empirical treatment for GERD be used? (2) with gastrointestinal GER symptoms, does treatment for GERD resolve the cough? (3) with or without gastrointestinal GER symptoms, what GER-based therapies should be used and for how long? (4) if GERD is suspected as the cause, what investigations and diagnostic criteria best determine GERD as the cause of the cough? METHODS: We used the CHEST Expert Cough Panel’s protocol and American College of Chest Physicians (CHEST) methodological guidelines and GRADE (Grading of Recommendations Assessment, Development and Evaluation) framework. Delphi methodology was used to obtain consensus. RESULTS: Few randomized controlled trials addressed the first two questions and none addressed the other two. The single meta-analysis (two randomized controlled trials) showed no significant difference between the groups (any intervention for GERD vs placebo for cough resolution; OR, 1.14; 95% CI, 0.45-2.93; P = .78). Proton pump inhibitors (vs placebo) caused increased serious adverse events. Qualitative data from existing CHEST cough systematic reviews were consistent with two international GERD guidelines. CONCLUSIONS: The panelists endorsed that: (1) treatment(s) for GERD should not be used when there are no clinical features of GERD; and (2) pediatric GERD guidelines should be used to guide treatment and investigations.